Natural Beauty: A GA Perspective - Dennis, Ian (Anthropoetics, 2021)
This essay explores the experience of natural beauty using the generative anthropology heuristic. Conceding that evidence of this form of aesthetic experience is almost inevitably textual and therefore mediated and distanced, it examines three suggestive accounts, by Francis Petrarch, William Wordsworth and Annie Dillard, as well as making briefer reference to other sources. The role of memory and imagination in these experiences is theorized, and the overall historical trend towards the wider and wider aestheticization of all perception is sketched.